2018
DOI: 10.18203/2320-1770.ijrcog20182481
|View full text |Cite
|
Sign up to set email alerts
|

A study to know clinical characteristics and outcome of obstetrics patients requiring ICU admission

Abstract: Background: Pregnancy poses unique consideration for critical care and it is imperative that obstetrician and other members of health care team have a working knowledge of these factors because these are women are usually young and in good health, their prognosis should be better than that of many other patients admitted to an intensive care.Methods: The present study was conducted in the Department of Obstetrics and Gynaecology, Gaja Raja Medical College and associate Kamla raja Hospital, Gwalior in the ICU f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In India, for instance, the maternal mortality ratio (MMR) in 2004 was 440/100,000 live births. However, a recent study by Garg and Tripatti (2018) showed that the MMR in Obstetric ICU was 6.34% which is similar to that reported by an Australian in 2010 (Karnad and Guntupalli, 2004).…”
Section: Introductionsupporting
confidence: 81%
“…In India, for instance, the maternal mortality ratio (MMR) in 2004 was 440/100,000 live births. However, a recent study by Garg and Tripatti (2018) showed that the MMR in Obstetric ICU was 6.34% which is similar to that reported by an Australian in 2010 (Karnad and Guntupalli, 2004).…”
Section: Introductionsupporting
confidence: 81%